Reflection on the Nutrition for Growth Summit 2025 and major takeaways - Covic, Namukolo M. (International Livestock Research Institute, 2025)
Namukolo Covic, ILRI Director General's Representative to Ethiopia, reflects on the summit and the significance of animal-source foods for nutrition for growth.